2002
DOI: 10.1113/jphysiol.2002.023317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhancement of human motor cortex excitability induced by interventional paired associative stimulation

Abstract: Associative stimulation has been shown to enhance excitability in the human motor cortex (Stefan et al. 2000); however, little is known about the underlying mechanisms. An interventional paired associative stimulation (IPAS) was employed consisting of repetitive application of single afferent electric stimuli, delivered to the right median nerve, paired with single pulse transcranial magnetic stimulation (TMS) over the optimal site for activation of the abductor pollicis brevis muscle (APB) to generate approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
472
4
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(537 citation statements)
references
References 41 publications
39
472
4
12
Order By: Relevance
“…It has been hypothesized that excessive inhibition following stroke may be related to a combination of dysregulation of intrinsic GABAergic interneurons and interhemispheric inhibition transmitted through crossed callosal fibers . Other research showed that repetitive stimulation to somatosensory cortex through the median nerve paired with TMS pulses delivered to motor cortex synergistically enhances the excitability of motor cortex [Stefan et al, 2002]. These results are consistent with a model of synaptic plasticity associated with LTP mediated by NMDA type glutamate receptors as studied in laboratory models.…”
Section: Enhancing Plasticity With Brain Stimulationsupporting
confidence: 77%
“…It has been hypothesized that excessive inhibition following stroke may be related to a combination of dysregulation of intrinsic GABAergic interneurons and interhemispheric inhibition transmitted through crossed callosal fibers . Other research showed that repetitive stimulation to somatosensory cortex through the median nerve paired with TMS pulses delivered to motor cortex synergistically enhances the excitability of motor cortex [Stefan et al, 2002]. These results are consistent with a model of synaptic plasticity associated with LTP mediated by NMDA type glutamate receptors as studied in laboratory models.…”
Section: Enhancing Plasticity With Brain Stimulationsupporting
confidence: 77%
“…Stimulation can either enhance or inhibit local neural activity (Stefan et al, 2000;Huang et al, 2005). The changes induced with these stimulation paradigms are thought to reflect long-term potentiation (LTP)-like or longterm depression (LTD)-like changes in synaptic efficacy (Stefan et al, 2002). rTMS can either be applied during a task (i.e., online), or before or after the task (i.e., offline).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…In a prior study, we compared two stimulation protocols for which robust effects have been described-paired associative stimulation (PAS) and theta burst stimulation (TBS)-and found that more consistent changes in motor cortical excitability were induced by PAS (Player et al, 2012). PAS-induced increases in cortical excitability are considered to be at least partially dependent on associative long-term potentiation (LTP) (Stefan et al, 2002), which is modulated by BDNF through both pre-and postsynaptic mechanisms (Yoshii and Constantine-Paton, 2010), known to be crucial for neuroplasticity. These mechanisms are believed to underlie motor learning and memory formation (Letzkus et al, 2007), hence providing an appropriate model for testing neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%